THE DEVELOPMENTAL STAGES OF THE ACQUISITION OF PAST TENSE-ASPECT MORPHOLOGY (Review of the literature) - ABOU EL FADL, Saber (PEOPLE: International Journal of Social Sciences, 2020)
This paper represents a conceptualization of L1 and L2 developmental stages of the acquisition of English past tense aspect verbal morphology. It constitutes the theoretical chapter of a PhD doctoral thesis that investigates the acquisition of past tense-aspect verbal morphology of EFL Moroccan university learners. The paper basically attempts to provide a recent review of related studies that account for the thesis topic. Primarily, it collects and reproduce the major and the prominent results that tackles the emergence of -ed and -ing past markers in the L1 and L2 context. Various studies attempted to give an understanding the nature of English past markers in different contexts adopting longitudinal or cross-sectional method, either in the natural environment or in the instructed one. Actually, this paper attempts to provide a consistent body of literature to account for the nature of the processes responsible for the emergence the tense-aspect system which differs from L1 to EFL context. Despite discrepancies in the findings, there’s still a consensus on the route of acquisition that seems to be similar among L1 and L2 learners with some respect. Therefore, most researchers seek to investigate the emergence of past tenses marking system through approaching how the interplay between the situational aspect and viewpoint aspect took place. However, this paper will focus on a prototype-based account to explain the nature of past tense-aspect acquisition development.